The Effect of Environmental, Social, and Governance (ESG) Disclosure on Basic Material Company Financial Performance - Sabrina, Dellya Assyifa; Sriyono, Sriyono; Yulianti, Retno (JURNAL ILMU MANAJEMEN, 2025)
Recent research results still differ regarding the development of Environmental, Social, and Governance Disclosure (ESG). Some studies show a positive trend of ESG in recent years. On the other hand, some studies show that ESG performance has a negative influence on the financial performance of basic material sector companies. This contradiction in findings is the basis for the author to explore the effect of ESG disclosure on the financial performance of Basic Material Sector Companies listed on the Indonesia Stock Exchange (IDX) during the period 2021-2023. Out of a total of 103 companies in this sector, only 34 companies reported ESG consistently during the period. This study uses a simple linear regression analysis model with company financial performance in the form of Tobin's Q as the dependent variable and ESG value as the independent variable. The results show that ESG disclosure is proven to have a positive effect on the company's financial performance. This finding is consistent with Stakeholder theory that companies that disclose ESG tend to have better performance because these disclosures strengthen relationships with key stakeholders, such as investors, customers, and communities, which in turn increase market confidence and firm value.